METODE DRILL AUDITORI TAKTIL ANAK TUNANETRA TERHADAP KEMAMPUAN MELAKUKAN KEGIATAN BERWUDHU ( SINGLE SUBJECT RESEARCH PADA SISWA TKLB DI SKH MADINA, SERANG-BANTEN) - Fani Fauziah; Dr. Hj. Isti Rusdiyani, M.Pd; Ratih Listyaningtyas, M.Pd (Jurusan Pendidikan Luar Biasa, FKIP Universitas Sultan Ageng Tirtayasa, 2018)
The use of tactile auditory drill methods to help make it easier for blind students to learn wudhu activities. This study aims to determine the effect of using tactile Auditory Drill method on the ability to perform Wudhu activities on blind children of TKLB students in Skh Madina Serang City. The method used in this study is the experimental method using the Single Subject Research approach, while the design used is design ABA. The collection technique used in this study was using tests, the tests used in this study were oral and tactile tests and analyzed by analysis in conditions and analysis between conditions. The target behavior in this study is to carry out the steps of wudhu activities. The results showed that there was an influence from the use of tactile auditory drill method in performing wudhu activities on blind children of TKLB in Madina SKH Serang City, with the acquisition of average values on target behavior (the accuracy of performing Wudhu activities steps) on average obtained at phase A1 (baseline 1) is 41.66%, in phase B (intervention) the average data obtained is 81.43%, then A1 (baseline 2) the average obtained is 55.29%.